THE INFLUENCE OF PROFITABILITY RATIO ON THE STOCK PRICE OF COMPANIES LISTED IN THE LQ45 INDEX - Nurbaiti; Putri Hasanah; Listyaningsih, Erna (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
The 45 most traded or highly liquid equities make up the LQ45 index, a stock index on the Indonesian Stock Exchange. Shares listed on the LQ45 Index change periodically according to the trading volume of the issuer's shares. Investors can analyze the financial performance of the LQ45 Index and one way to analyze financial performance is to use profitability ratios. The objects of this research are companies listed in the LQ45 index from 2020-2022. The firms that are regularly listed in the Indonesian Stock Exchange's LQ45 Index comprise the research population. Purposive sampling, which is nonprobability sampling, was the sample technique employed in this study. The study's findings indicate that stock prices are somewhat impacted by return on equity, or ROE.